INOVASI JELLY JAMU CEKOK TERSTANDAR SEBAGAI UPAYA PENANGANAN STUNTING; BERBASIS SOCIAL ENTERPRENEURSHIP - puspita sari, lutfiana; Mulati, Triwik Sri; Rahmawati, Muftika Khoiri; Rochmani, Sri (Universitas Nusantara PGRI Kediri, 2024)
Stunting remains a global nutritional issue for children. The prevalence of stunted children under five years old nationwide in Indonesia is 21.5%. One of the causes of stunting is due to appetite issues. The benefits of jamu cekok can increase appetite and boost immunity. However, the gift caused psychological trauma because it was given forcefully. The innovative work of jamu cekok made into jelly, a favorite food for children, but with the benefit of enhancing appetite and immunity. The Purpose is to address the issue of stunting and develop an entrepreneurial spirit among the community of Joton village, Jogonalan, Klaten. The jelly jamu cekok training activity was held for 2 days on June 3 and June 6, 2024, at the Dea Joton Hall, Jogonalan Klaten. Participants include all traditional health cadres and mothers of toddlers who have stunted or malnourished children, or even those with severe malnutrition. The first day's activities included training on making herbal jelly and materials on stunting, while the second day's activities focused on entrepreneurship training. The evaluation was conducted on June 18, 2024, to assess the jelly jamu cekok products made by the training participants. After conducting a 2-day training on making jelly jamu cekok and entrepreneurship, there was an increase in knowledge and skills among all participants. Additionally, toddlers with malnutrition and stunting who were given jelly jamu cekok showed an increase in appetite and a weight gain of approximately 1 kg within 2 weeks. The jelly jamu cekok and entrepreneurship training is effective in enhancing the knowledge and skills of cadres to address the issue of appetite in toddlers, which is the root cause of stunting, and can also increase community income from the sale of jelly jamu cekok.